(untitled) (Raparin Journal of Humanities (RJH), 2021)
The paper entitled (the derivational morphemes of agent nouns in Kurdish and English languages), is a comparative study. It intends to illustrate the construction of word formation of agent nouns in Kurdish and English languages. The paper consists of introduction and two chapters, also the results and references have been presented at the end of the research. The first chapter is about the grammatical rules and morphological process of derivational and inflectional morphemes. Then, the most significant derivational morphemes of agent nouns in Kurdish language have been displayed. In the second chapter, the most significant derivational morphemes of agent nouns of English language and their rules have been presented. Consequently, the most significant comparative and contrasts points of the derivational morphemes of agent nouns in both languages have been demonstrated.